Implementasi Model Pembelajaran Constraint-Led Approach dalam Meningkatkan Efektivitas Teknik Servis Atas pada Mata Kuliah Permainan Bolavoli - Ismawandi Bripandika Putra; Eka Kurnia Darisman; Achmad Nuryadi (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aimed to examine the effectiveness of the Constraint-Led Approach (CLA) learning model in improving overhand service skills in a volleyball course. A quasi-experimental design with a pretest–posttest control group design was employed. The participants were undergraduate students in a Physical Education program, divided into an experimental group and a control group. The experimental group received instruction using the CLA model, while the control group was taught using conventional teaching methods. The research instrument was a validated volleyball overhand service skill test. Data were analyzed using descriptive statistics and an Independent Sample T-Test. The results revealed a significant improvement in the experimental group compared to the control group. The posttest mean score of the experimental group was higher, and the statistical analysis showed a significant difference between groups (p < 0.05). These findings indicate that the Constraint-Led Approach is effective in enhancing students’ overhand service skills. In conclusion, CLA can be considered an effective and innovative learning model for teaching volleyball skills in higher education settings.